Primary teachers’ professional learning during a COVID-19 school lockdown - Mankki Ville; Räihä Pekka (Routledge, Taylor & Francis Group, 2022)
Background
The COVID-19 crisis forced education providers around the world to cancel contact teaching in schools as part of measures to limit contact between people and to slowdown the spread of the virus. The rapid and unexpected transition to distance teaching in the beginning of the pandemic posed an unprecedented challenge for teachers and placed a significant demand on their informal professional learning. This study focused on Finnish primary teachers’ professional learning domains and activities during the first weeks of Finland’s COVID-19 school lockdown.
Purpose
The aim was to understand what and how primary teachers learnt during the beginning of the distance teaching period.
Methods
Semi-structured interviews were conducted individually with 20 Finnish primary school teachers, all of whom had been delivering distance teaching from the beginning of the lockdown, during the fourth week of the distance teaching period. Two separate qualitative analyses were undertaken.
Findings
The first analysis indicated that teachers’ professional learning involved more than progress in the most self-evident and apparent technological knowledge domain: learning was also firmly connected to pedagogical knowledge and coping skills. The second analysis identified the individual learning activities, such as learning by doing, experimenting and considering one’s own teaching practice, and revealed three levels of collective learning activities (with a close colleague, in the school community and in larger online communities) carried out with the aim of improving distance teaching.
Conclusions
The study draws attention to primary teachers’ multifaceted professional learning domains and the activities entered into during the rapid shift from contact to distance teaching. It highlights that even in emergency circumstances, teachers’ individual and collective learning processes are interrelated and supplementary to each other. Educators’ hard-earned understanding achieved in relation to distance teaching should be nurtured and refined to further benefit and support the profession.